Unique effect of an electric field on a new liquid crystalline lactic acid derivative1. Issue 23 (21st June 2015) - Novotná, Vladimíra; Glogarová, Milada; Kašpar, Miroslav; Hamplová, Věra; Lejček, Lubor; Pociecha, Damian
<x xml:space="preserve">Abstract</x> A unique effect is observed in the TGBA phase under an applied electric field, which reversibly transforms the planar texture to a homeotropic one.